CHALLENGES IN THE SURGICAL MANAGEMENT OF BILATERAL POSTERIOR LENTIGLOBUS: Poster Presentation - Case Report - Resident - RAHMANI, SYIFA; Memed, Feti Karfiati; Caesarya, Sesy; Amiruddin, Primawita Oktarima; Irfani, Irawati; Kuntorini, Mayasari Wahyu (Majalah Oftalmologi Indonesia, 2023)
Introduction : Lentiglobus is a lens deformation characterized by spherical bulging of the lens surface. The weakness of the posterior capsule in the lentiglobus makes the surgery challenging. We present a case of bilateral posterior lentiglobus and its management. Case Illustration : A 5-year-old boy was presented with the chief complaint of gradually blurred vision since 1 year ago. Visual acuity were 0.1 and closed face finger counting in the right and left eyes, respectively. An ophthalmology examination revealed lens opacities with partially reabsorbed lens material and protrusion of the lens surface posteriorly in both eyes (figure 1). The patient was diagnosed with developmental cataracts of the membranous type and posterior lentiglobus in both eyes. The patient underwent a surgical intervention for cataract extraction with aspiration technique. A spontaneous posterior capsule rupture was found with a shape like a lentiglobus. An anterior vitrectomy was performed. An intraocular lens was implanted. At one month after surgery, the best corrected visual acuities were 0.5 in both eyes (figure 2). Discussion : Several difficulties can be encountered during pediatric cataract surgery with the posterior lentiglobus morphology because of the thin or ruptured capsule. Previous studies have found preoperative and intraoperative posterior capsule rupture in 25% and 3.13% of lentiglobus cases, respectively. Hydrodissection should be avoided due to the weakness of the posterior capsule. ConclusionAppropriate surgical techniques to anticipate posterior capsule defects in the lentiglobus are required to produce a favorable outcome.